Many-body interatomic U and Al-U potentials - Pascuet, Maria Ines Magdalena (2012)
In the present work, an interatomic potential in the framework of the embedded atom method (EAM) is developed for the Al–U binary system. A methodology is detailed to fit the U potential that reproduces the stability of the a phase at low temperatures and the g phase at high ones. The thermal stability of both phases, thermal expansion and vacancy driven self diffusion are studied. The Al–U potential is fit to first principles calculated formation energies of the experimentally observed intermetallic phases, Al2U (cubic C15), Al3U (cubic L12) and Al4U (orthorhombic D1b). As a first validation the potentials are tested against available experimental measurements.